Inaccuracy in Indonesian Subtitles of The Kingâ€™s Speech Movie (2010) - Burliani, Dessy; Winiharti, Menik (Lingua Cultura, 2016)
Movie subtitles is a product of translations, so the rules of translations must be followed. The research explored how translation mistakes in Indonesian subtitles of â€œThe Kingâ€™s Speechâ€ Movie (2010) and distort the meaning of the original utterances. The data were the dialogues in English and their Indonesian translations. Qualitative method was applied in this research. The analysis was done by comparing the meaning of the original utterances and their Indonesian subtitles. It is found that the types of mistakes that mostly occurred in the Indonesian subtitles of the movie were ambiguity and omission mistakes. To avoid these mistakes, the context of the original utterance must be considered. In general, it can be concluded that accuracy in subtitling should be taken into account.